2005
DOI: 10.1373/clinchem.2005.051565
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infection: A Risk Factor for False-Negative Urinary Ethyl Glucuronide but Not Ethyl Sulfate in the Detection of Recent Alcohol Consumption

Abstract: After consumption of alcoholic beverages, the bulk of the ethanol dose (95%-98%) is eliminated in a 2-stage oxidation process mainly in the liver, first to acetaldehyde by alcohol dehydrogenase and then further to acetic acid by aldehyde dehydrogenase. The remainder is excreted unchanged in urine, sweat, and expired air (1 ). In addition, a very small fraction (Ͻ0.1%) of the ingested ethanol undergoes phase II conjugation reactions to produce ethyl glucuronide (EtG) and ethyl sulfate (EtS) (2, 3 ), catalyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 22 publications
(28 reference statements)
8
96
0
4
Order By: Relevance
“…Both our study (paper II) and others have documented that EtG is unstable in the presence of bacteria, both in post mortem material (115,119) and in clinical urine samples (146,147 Weinmann, personal information). We found that refrigeration and the presence of preservatives made EtG stable (paper II), results that are also supported by other publications (146,148).…”
Section: Use Of Etg and Ets As A Marker Of Ante Mortem Alcohol Ingestsupporting
confidence: 65%
See 2 more Smart Citations
“…Both our study (paper II) and others have documented that EtG is unstable in the presence of bacteria, both in post mortem material (115,119) and in clinical urine samples (146,147 Weinmann, personal information). We found that refrigeration and the presence of preservatives made EtG stable (paper II), results that are also supported by other publications (146,148).…”
Section: Use Of Etg and Ets As A Marker Of Ante Mortem Alcohol Ingestsupporting
confidence: 65%
“…Both our study (paper II) and others have documented that EtG is unstable in the presence of bacteria, both in post mortem material (115,119) and in clinical urine samples (146,147 Weinmann, personal information). We found that refrigeration and the presence of preservatives made EtG stable (paper II), results that are also supported by other publications (146,148). It is also well documented that EtS is stable in the presence of bacteria, both in clinical urine samples and post mortem material (119,146,147), although a very recent publication showed some instability under extreme conditions, also of EtS (149).…”
Section: Use Of Etg and Ets As A Marker Of Ante Mortem Alcohol Ingestsupporting
confidence: 65%
See 1 more Smart Citation
“…Another study has also shown that EtG levels were concordant with alcohol intake habits [15]. However, it has been suggested that due to false negative results during putrefaction, it has to be interpreted carefully and it was suggested to use both EtG and EtS to be more accurate [104,105]. However, as EtG degradation and also possible artifactual formation both require microbial activity, VH is expected to be less prone to false positive and false negative EtG results [106][107].…”
Section: Alcohol and Drugsmentioning
confidence: 99%
“…In addition, samples can be taken into containers with fluoride preservatives and frozen to prevent bacterial growth. 22 Other preservatives, e.g. boric acid, have not been investigated with respect to EtG.…”
Section: Causes Of False-positive or -Negative Resultsmentioning
confidence: 99%